2021
DOI: 10.1002/bem.22337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long‐Term Exposure of Intermediate Frequency Magnetic Fields (20 kHz, 360 µT) on the Development, Pathological Findings, and Behavior of Female Mice

Abstract: The use of magnetic fields in the intermediate-frequency (IF) range to wirelessly charge electric cars with power transfer in the kilowatt range has become increasingly widespread, leading to unavoidable stray fields in the microtesla range. Only a handful of studies have assessed the potential biological risks associated with exposure to such fields. We exposed female mice (n = 80 per group) to either 20 kHz, 360 μT (rms), or sham in Helmholtz coils to conduct a blind design study. Exposure started at 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The results indicated that exposure at 20 kHz, 360 μT did not have adverse effects on tumor development and incidence. However, significant differences in behavioral tests suggested a potentially higher level of alertness in mice ( 14 ).…”
Section: Related Workmentioning
confidence: 99%
“…The results indicated that exposure at 20 kHz, 360 μT did not have adverse effects on tumor development and incidence. However, significant differences in behavioral tests suggested a potentially higher level of alertness in mice ( 14 ).…”
Section: Related Workmentioning
confidence: 99%
“…This RF belongs to Group 2B on the carcinogenic hazard identification of IARC [14]. Many in vivo and in vitro studies have also been conducted on exposure to magnetic fields in the intermediate frequency (IF; 300 Hz to 10 MHz) range [15][16][17][18][19][20][21][22][23]. Most reports showed no effect after exposure to IF magnetic fields, although some studies have shown an increase in oxidative stress markers [20].…”
Section: Introductionmentioning
confidence: 99%